Pore‐forming toxin‐like protein complex expressed by frog promotes tissue repair. Issue 1 (31st July 2018) - Gao, Zhen-Hua; Deng, Cheng-Jie; Xie, Yue-Ying; Guo, Xiao-Long; Wang, Qi-Quan; Liu, Ling-Zhen; Lee, Wen-Hui; Li, Sheng-An; Zhang, Yun
ABSTRACT: Tissue repair is a highly dynamic process, and the immediate onset of acute inflammation has been considered necessary for repair. Pore‐forming proteins are important, both in pathogen invasion and host immunity. However, their roles in wound healing and tissue repair are unclear. βγ‐crystallin fused aerolysin‐like protein (α‐subunit) and trefoil factor (β‐subunit) complex (βγ‐CAT) is a complex of a bacterial pore‐forming toxin aerolysin‐like protein and trefoil factor identified in the frog Bombina maxima . In this study, we established mouse cutaneous wound models to explore the effects of βγ‐CAT on skin wound healing. βγ‐CAT accelerated the healing of full‐thickness wounds by improving re‐epithelialization. This complex relieved dermal edema and promoted scarless healing. βγ‐CAT treatment resulted in a rapid release of IL‐1β, which initiated an acute inflammation response in the early stage of healing. Meanwhile, the expression levels of TGF‐β1, VEGF, and bFGF and the recruitment of M2 macrophages around the wound significantly increased after βγ‐CAT treatment. βγ‐CAT protected skin wounds against methicillin‐resistant Staphylococcus aureus by improving neutrophil recruitment at the site of the wound. Overall, our results suggest that βγ‐CAT can promote tissue repair and protect skin wounds against antibiotic‐resistant bacterial infection by triggering the acute inflammatory response. This is the first example that aerolysin‐like pore‐forming proteins widely existing in plants and animals may act in wound healing and tissue repair.—Gao, Z.‐H., Deng, C.‐J., Xie, Y.‐Y., Guo, X.‐L., Wang, Q.‐Q., Liu, L.‐Z., Lee, W.‐H., Li, S.‐A., Zhang, Y., Pore‐forming toxin‐like protein complex expressed by frog promotes tissue repair. FASEB J. 33, 782–795 (2019). www.fasebj.org